Сучасне праворозуміння у світлі ціннісних орієнтацій права - Львова, О.Л. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются вопросы современного понимания права в контексте его ценностных ориентаций. Анализируются юридико-позитивистская и природно-правовая концепции права, проводится сопоставление права и закона, раскрывается содержание правового закона и его роль в демократическом правовом государстве. In this article the questions of the modern understanding of right are examined in the context of its valued orientations. In particular, legally-positive and natural-legal conceptions of right are analysed, comparison of right and law is conducted, maintenance of legal law and its role opens up in the democratic legal state.